Analysis of C9orf72 in patients with frontotemporal dementia and amyotrophic lateral sclerosis from Argentina - Itzcovich, Tatiana (2016)
Pathologic expansion of the G4C2 repeat in C9orf72 is the main genetic cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS). To evaluate the frequency of the G4C2 expansion in a Latin American cohort of FTD and ALS patients, we used a 2-step genotyping strategy. For FTD, we observed an overall expansion frequency of 18.2% (6 of 33 unrelated cases). Moreover, the C9orf72 expansion accounted for 37.5% of all familial FTD cases (6 of 16 families). The expansion frequency in sporadic ALS cases was 2% (1 of 47 unrelated patients), whereas we observed the expansion in 1 of 3 families with a positive history for ALS. Overall, the expansion frequency in our FTD group was similar to that reported for patients in Europe and North America, whereas the frequency in our sporadic ALS group was significantly lower. To our knowledge, this is the first report on the frequency of the C9orf72 expansion in a Latin American population.